Factors affecting Technology transfer performance in the Petrochemical Industry in Thailand: A Case study - Distanont, Anyanitha; Khongmalai, Orapan; Kritpipat, Pranee (WMS Journal of Management, 2018)
The Petrochemical Industry in Thailand relies on the importance of technology transfer from the more advanced companies in order to develop its production process and competitive ability. However, technology transfer from one country to another country or from one company to another relies on several factors regarding technology sender and recipient. These factors clearly affect the effectiveness of technology transfer. Therefore, this research study aims to investigate the factors influencing the performance of technology transfer in the petrochemical industry in Thailand. This study is a quantitative study using questionnaires as a tool to collect data. Data is analyzed through the Exploratory Factor Analysis (EFA) technique and the Structure Equation Model (SEM). The research findings shows that the crucial factors influencing the performance of technology transfer are: 1) absorptive capacity, 2) partner characteristics, 3) the complexity of technology, and 4) inter-organizational relationships. These factors are grouped into two groups, namely human-oriented factors and technology-oriented factors. This research contributes to a better understanding of technology transfer in the pharmaceutical industry context. These findings can be used as the basis for technology transfer process development in Thailand.